Music Creation Lwah Solas | Kreasi Musik Lwah Solas - I Gusti Bagus Putra Yata (GHURNITA: Jurnal Seni Karawitan, 2024)
Lwah Solas is a Creative Musical Work inspired by 11 (eleven) springs or rivers that meet to become one, which gives a source of life for living things, but on the other hand, also brings crash and destroy everything. The stylist tries to process ideas into a karawitan work that is still based on the concept tradition, where in the arrangement, prioritizing internal techniques gamelan Gong Kebyar such as Kekotekan, Norot, nyogcag and in some parts it uses eleven beats. Techniques processed in such a way and still firmly rooted in the essence of tradition, which has become the foundation of composing. tetekep, gegebug, and expressions become an essential reference into a unified whole and the concept of deep musical arrangement Balinese fussiness. It is essential to create Tabuh Kreasi Lwah Solas because of the large amount of pollution of springs by humans that is happening nowadays. From here, the stylist created the percussion creations of Lwah Solas to remind the public to protect, respect, and sanctify the existing springs because springs are the main element for human survival.